Ethnic and border differences on blood cancer presentation and outcomes: A Texas population‐based study. Issue 7 (3rd December 2020) - Bencomo‐Alvarez, Alfonso E.; Gonzalez, Mayra A.; Rubio, Andres J.; Olivas, Idaly M.; Lara, Joshua J.; Padilla, Osvaldo; Orazi, Attilio; Corral, Javier; Philipovskiy, Alexander; Gaur, Sumit; Mulla, Zuber D.; Dwivedi, Alok K.; et al.
Abstract : Background: The Texas/Chihuahua (US/Mexico) border is a medically underserved region with many reported barriers for health care access. Although Hispanic ethnicity is associated with health disparities for many different diseases, the population‐based estimates of incidence and survival for patients with blood cancer along the border are unknown. The authors hypothesized that Hispanic ethnicity and border proximity is associated with poor blood cancer outcomes. Methods: Data from the Texas Cancer Registry (1995‐2016) were used to investigate the primary exposures of patient ethnicity (Hispanic vs non‐Hispanic) and geographic location (border vs non‐border). Other confounders and covariates included sex, age, year of diagnosis, rurality, insurance status, poverty indicators, and comorbidities. The Mantel‐Haenszel method and Cox regression analyses were used to determine adjusted effects of ethnicity and border proximity on the relative risk (RR) and survival of patients with different blood cancer types. Results: Hispanic patients were diagnosed at a younger age than non‐Hispanic patients and presented with increased comorbidities. Whereas non‐Hispanics had a higher incidence of developing blood cancer compared with Hispanics overall, Hispanics demonstrated a higher incidence of acute lymphoblastic leukemia (RR, 1.92; 95% CI, 1.79‐2.08; P < .001) with worse outcomes. Hispanics from the Texas/Chihuahua border demonstrated a higher incidence of chronic myeloid leukemia (RR, 1.28; 95% CI, 1.07‐1.51; P = .02) and acute myeloid leukemia (RR, 1.17; 95% CI, 1.04‐1.33; P = .0009) compared with Hispanics living elsewhere in Texas. Conclusions: Hispanic ethnicity and border proximity were associated with a poor presentation and an adverse prognosis despite the younger age of diagnosis. Future studies should explore differences in disease biology and treatment strategies that could drive these regional disparities. Abstract : Hispanic patients with blood cancer are diagnosed at a younger age, have poor presentation, and have worse prognoses compared with non‐Hispanic patients. Hispanics with acute lymphocytic leukemia, acute myeloid leukemia, or chronic myelogenous leukemia who are diagnosed near the Texas/Chihuahua border have worse outcomes compared with Hispanics living elsewhere.